Adhesive composition

JP2025024290APending Publication Date: 2025-02-20TOSOH CORP
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
JP2023128294
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-07
Publication Date
2025-02-20

AI Technical Summary

Benefits of technology

【0011】 本発明により、優れた粘接着特性を示す粘着剤組成物を提供することができる。より具体的に言えば、タック(初期接着力)、粘着力及び保持力のバランスに優れたホットメルト系粘着剤組成物を提供することができ、工業的にも非常に有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025024290000001
    Figure 2025024290000001
  • Figure 2025024290000002
    Figure 2025024290000002
Patent Text Reader

Abstract

To provide an adhesive composition which has good tack (initial adhesive strength), adhesive strength and holding power and is particularly useful as a hot-melt adhesive.SOLUTION: The adhesive composition contains 10-100 pts.mass of a process oil and 60-150 pts.mass of a cycloolefin copolymer based on 100 pts.mass of a thermoplastic elastomer. The cycloolefin copolymer has a softening point of 60-120°C, a bromine value of 10-60, and a number average molecular weight of 800-5,000.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a hot melt pressure sensitive adhesive composition having a thermoplastic elastomer as a base polymer. [Background technology]

[0002] Adhesives can be bonded by applying only slight pressure for a short time at room temperature without using water, solvents, or heat. Adhesives are applied to plastic films, cellophane, paper, cloth, etc., and are processed and used in a variety of adhesive products such as various adhesive tapes and adhesive labels and sheets.

[0003] Adhesives are made up of various polymer elastomers as a base, and as necessary, tackifiers, crosslinking agents, stabilizers, plasticizers, etc. Among them, natural rubber-based adhesives, which dissolve natural rubber, tackifiers, softeners, etc. in solvents such as toluene, have dominated the rubber-based adhesive market due to their excellent tack (initial adhesive strength) and low- and high-temperature properties. However, the market for hot-melt adhesives, which use thermoplastic elastomers as a base polymer, is expanding due to their fast application speed during manufacturing, no need for solvent recovery or drying, no risk of fire, and no pollution of the air or work environment.

[0004] Known hot melt pressure sensitive adhesives are pressure sensitive adhesive compositions comprising a styrene-isoprene-styrene block copolymer as a base polymer, to which a tackifier and, if necessary, a softener such as naphthenic oil or paraffinic oil are added.

[0005] On the other hand, cycloolefin polymers are used mainly in optical components as a substitute for glass due to their excellent optical properties and low moisture absorption, and are also used in medical containers and semiconductor containers due to their moldability and light weight.

[0006] It is known that a low molecular weight cycloolefin polymer having a number average molecular weight (Mn) of 10,000 to 50,000 and a molecular weight distribution dispersity (Mw / Mn) of 2.0 to 10.0 can be produced by melting a cycloolefin polymer (number average molecular weight of 30,000 or more) and pyrolyzing it at 330 to 380°C (see, for example, Patent Document 1). [Prior art documents] [Patent documents]

[0007] [Patent Document 1] Patent No. 6083597 Summary of the Invention [Problem to be solved by the invention]

[0008] The low molecular weight cycloolefin polymer described in Patent Document 1 has poor affinity with polymer elastomers, and therefore when used in a hot melt pressure sensitive adhesive composition having a thermoplastic elastomer as a base polymer, it does not exhibit adhesive performance with an excellent balance of tack (initial adhesive strength), adhesive strength and holding power. [Means for solving the problem]

[0009] Means for Solving the Problems The present inventors have conducted intensive research to solve the above problems and have found that a pressure-sensitive adhesive composition containing a cycloolefin copolymer having specific physical properties exhibits excellent adhesive properties, thereby completing the present invention.

[0010] That is, the respective aspects of the present invention are as follows [1] to [2]. [1] A pressure-sensitive adhesive composition comprising 10 to 100 parts by mass of a process oil and 60 to 150 parts by mass of a cycloolefin copolymer relative to 100 parts by mass of a thermoplastic elastomer, wherein the cycloolefin copolymer has a softening point of 60 to 120°C, a bromine number of 10 to 60, and a number average molecular weight of 800 to 5,000. [2] The pressure-sensitive adhesive composition according to [1], wherein the thermoplastic elastomer is a styrene-isoprene-styrene block copolymer. Effect of the Invention

[0011] The present invention can provide a pressure-sensitive adhesive composition exhibiting excellent adhesive properties, more specifically, a hot-melt pressure-sensitive adhesive composition having an excellent balance of tack (initial adhesive strength), adhesive strength, and holding power, which is very useful industrially. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] The present invention will be described in detail below based on preferred embodiments thereof.

[0013] The pressure-sensitive adhesive composition according to one embodiment of the present invention contains a thermoplastic elastomer, a process oil as the oil, and a cycloolefin copolymer as the tackifier.

[0014] The thermoplastic elastomer in the present invention is not particularly limited, and examples thereof include styrene-based thermoplastic elastomers such as styrene-isoprene-styrene block copolymers, styrene-butadiene-styrene block copolymers, and styrene-ethylene-butylene-styrene block copolymers; olefin-based thermoplastic elastomers such as ethylene-vinyl acetate copolymers; urethane-based thermoplastic elastomers; and polyester-based thermoplastic elastomers. Among these, styrene-based thermoplastic elastomers are preferred, and styrene-isoprene-styrene block copolymers are particularly preferred.

[0015] Styrene-isoprene-styrene block copolymers are used as base polymers for adhesives, and their basic structure is a so-called ABA type block structure having polystyrene end blocks (hard segments) and rubber-like polyisoprene mid blocks (soft segments) at both ends. Here, the polystyrene block and the polyisoprene block are not easily compatible with each other, so they form a microphase separation structure at room temperature. That is, due to the formation of polystyrene domains, the polyisoprene chains are physically crosslinked. The crosslinked structure due to the formation of polystyrene domains disappears at high temperatures above the glass transition temperature of polystyrene, and the styrene-isoprene-styrene block copolymer transitions from a rubber state to a molten state. That is, since it exhibits thermoplasticity, it is possible to perform hot melt processing, and it is particularly preferably used as a base polymer for adhesives.

[0016] The softening point of the cycloolefin copolymer is preferably 60 to 120° C., more preferably 80 to 110° C., in accordance with JIS K-2207, since this provides excellent compatibility with the rubber component and processability.

[0017] The cycloolefin copolymer may contain a carbon-carbon double bond. As an index of this, the bromine number measured according to JIS K-2605 (1996) is 10 to 60 (g-Br2 / 100g). If the bromine number is 60 or less, the cycloolefin copolymer has excellent heat resistance and is less likely to develop coloration due to thermal decomposition.

[0018] The number average molecular weight of the cycloolefin copolymer is 800 to 5000, and preferably 800 to 3000. When the number average molecular weight is within this range, compatibility with rubber is good.

[0019] The cycloolefin copolymer is preferably a copolymer containing a cycloalkene having a norbornene skeleton and a non-cyclic monoolefin as constituent monomers.

[0020] Examples of the cycloalkene having a norbornene skeleton include monocycloalkenes having 7 to 25 carbon atoms and a norbornene skeleton {norbornene (bicyclo[2.2.1]-2-heptene), tricyclo[4.3.0.1 2,5 ]-3-decene, 8-ethyl-tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, tricyclo[4.3.0.1 2,5 ]-3-decene, tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, pentacyclo[6.5.1.1 3,6 .0 2,7 .0 9,13 ]-4-Pentadecene, Pentacyclo[7.4.0.1 2,5 .1 9,12 .0 8,13 ]-3-Pentadecene, Pentacyclo[8.4.0.1 2,5 .1 9,12 .0 8,13 ]-3-Hexadecene, Pentacyclo[6.6.1.1 3,6 .0 2,7 .0 9,14 ]-4-Hexadecene, Hexacyclo[6.6.1.1 3,6 .1 10,13 .0 2,7 .0 9,14 ]-4-Heptadecene, Hexacyclo[6.6.1.1 3,6 .1 10,13 .0 2,7 .0 9,14 ]-4-Heptadecene, Heptacyclo[8.7.0.1 2,9 .1 4,7 .1 11,17 .0 3,8 .0 12,16 ]-5-Eicosene, heptacyclo[8.7.0.1 3,6 .1 10,17 .1 12,15 .0 2,7 .0 11,16 ]-4-Eicosene, heptacyclo[8.7.0.1 3,6 .1 10,17 .1 12,15 .0 2,7 .0 11,16]-4-Eicosene, heptacyclo[8.8.0.1 2,9 .1 4,7 .1 11,18 .0 3,8 .0 12,17 ]-5-Henneicosene, Octacyclo[8.8.0.1 2,9 .1 4,7 .1 11,18 .1 13,16 .0 3,8 .0 12,17 ]-5-docosene, and nonacyclo[10.9.1.1 4,7 .1 13,20 .1 15,18 .0 2,10 .0 3,8 .0 12,21 .0 14,19 ]-5-pentacosene.

[0021] Among the above cycloalkenes having a norbornene skeleton, preferred are tricyclo[4.3.0.1 2,5 ]-3-decene, 8-ethyl-tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, tetracyclo[4.4.0.1 2,5 .1 7,10 ]-3-dodecene, norbornene (bicyclo[2.2.1]-2-heptene).

[0022] The acyclic monoolefin is preferably acyclic monoolefin having 2 to 10 carbon atoms.

[0023] Among the acyclic monoolefins having 2 to 10 carbon atoms, those having 4 or more carbon atoms are acyclic monoolefins having a double bond at the terminal. Examples of these acyclic monoolefins include ethylene, propylene, and α-olefins having 4 to 8 carbon atoms (1-butene, 1-pentene, 1-hexene, 1-heptene, 1-octene, etc.). Among these, ethylene and propylene are preferred.

[0024] The molar ratio of the cycloalkene having a norbornene skeleton to the non-cyclic monoolefin constituting the cycloolefin copolymer [cycloalkene / olefin] varies depending on the target resin, but is preferably 2 / 98 to 80 / 20, more preferably 5 / 95 to 70 / 30, and particularly preferably 10 / 90 to 60 / 40.

[0025] The cycloolefin copolymer can be produced by melting a cycloolefin polymer containing a cycloalkene having a norbornene skeleton and a non-cyclic monoolefin as constituent monomers, and pyrolyzing the melted polymer at 300 to 450°C.

[0026] A preferred method for adjusting the cycloolefin copolymer to have the above number average molecular weight is to reduce the molecular weight by subjecting the cycloolefin polymer to a thermal decomposition reaction to partially cleavage of the main chain.

[0027] The cycloolefin polymer can be any cycloolefin polymer having a number average molecular weight of 10,000 to 200,000, which is composed of the cycloalkene having a norbornene skeleton and the acyclic monoolefin, and is not limited thereto. Commercially available products (e.g., Zeonex series and Zeonor series manufactured by Zeon Corporation, Apel series manufactured by Mitsui Chemicals, Inc., and TOPAS series manufactured by Polyplastics Co., Ltd.) may also be used.

[0028] The pyrolysis is preferably carried out in an atmosphere of a gas that is not reactive with the cycloolefin polymer (hereinafter referred to as an inert gas) at 300 to 450° C. for 0.5 to 10 hours. Specific examples of the inert gas include argon, nitrogen, carbon dioxide, and water vapor, and nitrogen is preferred. The inert gas is preferably passed through the reaction vessel at a flow rate of 0.1 to 100 L / min during heating.

[0029] The heating temperature is preferably 300 to 450° C., more preferably 320 to 450° C. When the reaction temperature is within this range, the coloring of the cycloolefin copolymer is reduced and the generation of odor is suppressed, which is preferable. Hereinafter, the fact that the coloring is reduced and the generation of odor is suppressed is referred to as "good color tone and odor."

[0030] The reaction time is preferably 0.5 to 10 hours, more preferably 1 to 7 hours. When the reaction time is within this range, the color and odor of the unsaturated bond-containing cycloolefin copolymer become good, and homogeneous thermal decomposition can be achieved, which is preferable.

[0031] The pressure for pyrolysis is preferably normal pressure (atmospheric pressure) to 20 MPa, more preferably normal pressure to 150 MPa. Within this range, the color tone and odor of the unsaturated bond-containing cycloolefin copolymer become good.

[0032] The thermal decomposition method may be either a batch method or a continuous method.

[0033] When using a batch method, the process can be carried out by passing an inert gas through a reaction vessel made of stainless steel or the like equipped with a stirrer, placing the raw material cycloolefin polymer in the reaction vessel, and heating the reaction vessel at a predetermined temperature for a predetermined period of time while stirring.

[0034] When a continuous process is used, an inert gas is passed through a continuous reaction vessel such as a tubular reactor or an extruder, the raw material cycloolefin polymer is placed in the reaction vessel, and the raw material is heated and melted while adjusting the amount of the raw material introduced so that the raw material remains in the reaction vessel at a predetermined temperature for a predetermined time, thereby carrying out thermal decomposition.

[0035] The thermal decomposition may be carried out by adding a phenol-based antioxidant. Examples of the phenol-based antioxidant include hindered phenol compounds such as 2,6-di-tert-butyl-4-methylphenol, 2-tert-butyl-4-methylphenol, 6-tert-butyl-2,4-methylphenol, 2,6-di-tert-butylphenol, and 2-tert-butyl-4-ethylphenol.

[0036] In the thermal decomposition, a catalyst can be used to promote the decomposition reaction. Examples of the catalyst to be added include radical generating catalysts [peroxides such as benzoyl peroxide, di-tert-butyl peroxide, and dicumyl peroxide; azonitriles such as 2,2'-azobis(isobutyronitrile), 2,2'-azobis(2,4-dimethylvaleronitrile), and 4,4'-azobis(4-cyanovaleric acid)] and cracking catalysts (silica-alumina, silica-magnesia, activated clay, etc.).

[0037] The process oil is used to lower the melt viscosity of the adhesive and to improve tack and plasticity. There are no particular limitations on the process oil used, and examples thereof include paraffinic oil, naphthenic oil, and the like.

[0038] In the pressure-sensitive adhesive composition, the blending ratio of each component is 60 to 150 parts by mass, preferably 70 to 130 parts by mass of cycloolefin copolymer and 10 to 100 parts by mass, preferably 30 to 70 parts by mass of process oil, per 100 parts by mass of thermoplastic elastomer.

[0039] In the present invention, it is preferable to blend an antioxidant in the pressure-sensitive adhesive composition in order to impart heat durability. The blending amount is preferably 2 parts by mass or less, particularly preferably 1 part by mass or less, per 100 parts by mass of the thermoplastic elastomer. The specific antioxidant is not particularly limited as long as it is one that is generally used as an antioxidant in the field of pressure-sensitive adhesives, and an example of the antioxidant is Irganox 1010.

[0040] The method for producing the pressure-sensitive adhesive composition is not particularly limited as long as a pressure-sensitive adhesive composition can be obtained, and examples of the method include a method in which each compounding component is charged into a blade mixer equipped with a blade having a suitable shape for kneading and heated and kneaded to produce a production method, a continuous production method using an extruder-type kneader equipped with a single- or twin-screw, etc. Also, each compounding component can be stirred and mixed in the presence of a solvent such as toluene to produce a pressure-sensitive adhesive solution, and further, a hydrocarbon resin previously emulsified in a rubber latex can be stirred and mixed to produce a pressure-sensitive adhesive emulsion.

[0041] The above-mentioned adhesive composition is an adhesive composition having good tack (initial adhesive strength), adhesion and holding power; specifically, the tack is preferably 6 ball No. or more, and particularly preferably 10 ball No. or more, the adhesion is preferably 7 N / 25 mm or more, and particularly preferably 9 N / 25 mm or more, and the holding power is preferably 50 minutes or more, and particularly preferably 200 minutes or more.

[0042] The adhesive composition of the present invention is usually applied to a desired substrate using a coater to produce various adhesive tapes or adhesive label products. EXAMPLES

[0043] The present invention will be described below with reference to examples, but the present invention is not limited to these examples. The analytical and test methods used in the examples and comparative examples are as follows.

[0044] The analytical methods for cycloolefin copolymers are shown below.

[0045] ~Measurement of weight average molecular weight (Mw) and number average molecular weight (Mw)~ Polystyrene was used as the standard substance and measurements were performed by gel permeation chromatography in accordance with JIS K-0124 (2011).

[0046] ~Bromine number~ The measurement was performed according to a method conforming to JIS K-2605 (1996).

[0047] ~Softening point~ The measurement was performed according to JIS K-2207 (1996) (Ball and Ring Method).

[0048] The method and criteria for evaluating the adhesive properties of the pressure-sensitive adhesive composition are shown below.

[0049] ~Tuck~ In accordance with JIS Z-0237, a 10 cm long ball was attached with the adhesive side facing up to a slope on a glass plate with an inclination angle of 30 degrees at 23°C, and 31 different sizes of steel balls, ranging from 1 / 16 inch to 1 inch in diameter, were rolled from a position 10 cm above the slope at an initial speed of 0 and the size of the largest ball that came to rest on the adhesive tape was expressed as the size (unit: ball No. [= x 1 / 32 inch]).

[0050] ~Adhesive power~ In accordance with JIS Z-0237, an adhesive tape measuring 25 mm wide x 100 mm long was attached to cardboard and peeled off in a 180 degree direction at a speed of 300 mm / min at 23°C to measure the peel force (unit: N / 25 mm).

[0051] ~Holding power~ In accordance with JIS Z-0237, adhesive tape was attached to cardboard over an area of ​​25 mm x 25 mm, and a load of 1 kg was applied at 50°C to measure the time (unit: minutes) required for the adhesive tape to fall off the cardboard. Manufacturing Example 1 A small quartz pyrolysis device was used as the pyrolysis device. 10 g of cycloolefin polymer (ZEON Corporation, ZEONEX690R, Mn 15,000) was charged into the pyrolysis device, and the system was replaced with nitrogen, and then heated to melt at an internal temperature of 385°C. After 25 minutes, the system was cooled to room temperature, and the reaction system was returned to normal pressure. The residue in the pyrolysis device was dissolved in hot xylene, and then dropped into methanol for reprecipitation and purification, to obtain cycloolefin copolymer A. The evaluation results are shown in Table 1.

[0052] Manufacturing Examples 2 to 4 Cycloolefin copolymers B to D were obtained in the same manner as in Production Example 1, except that the pyrolysis conditions (temperature, time) and the type of cycloolefin polymer were as shown in Table 1. The evaluation results are shown in Table 1. TOPAS6013M-07 (Mn 50,000) is a cycloolefin polymer manufactured by Polyplastics Co., Ltd.

[0053] [Table 1]

[0054] Example 1 A pressure-sensitive adhesive composition containing 100 parts by mass of a styrene-isoprene-styrene block copolymer (Kraton D1163, manufactured by Kraton Polymers, hereinafter abbreviated as SIS) as a thermoplastic elastomer, 100 parts by mass of cycloolefin copolymer A, 50 parts by mass of naphthenic process oil (SNH100, manufactured by Sankyo Yuka Kogyo Co., Ltd.), and 1 part by mass of an antioxidant (Irganox 1010, manufactured by BASF) was prepared by a hot melt method. Specifically, SIS, cycloolefin copolymer A, and the antioxidant were charged into a nitrogen-substituted stirring blade type kneader at 160°C, and when the pellet-like shape of the SIS disappeared, the process oil was charged to obtain a pressure-sensitive adhesive composition.

[0055] After stirring for about 20 minutes, the resulting adhesive composition was applied to a 25 μm thick polyester film on a hot plate at 160° C. using a hot melt applicator to prepare an adhesive sheet with a thickness of 20 μm, and the tack (initial adhesive strength), adhesive strength and holding strength of the sheet were measured. The results are shown in Table 2.

[0056] [Table 2]

[0057] Examples 2 to 3 Pressure-sensitive adhesive compositions were prepared and evaluated in the same manner as in Example 1, except that cycloolefin copolymers B and C were used instead of cycloolefin copolymer A. The results are shown in Table 2.

[0058] Examples 4 to 5 Pressure-sensitive adhesive compositions were prepared and evaluated in the same manner as in Example 1, except that cycloolefin copolymer B was used in place of cycloolefin copolymer A in the amounts shown in Table 2. The results are shown in Table 2.

[0059] Examples 6 to 7 PSA compositions were prepared and evaluated in the same manner as in Example 2, except that the naphthenic oil was used in the amount shown in Table 2. The results are shown in Table 2.

[0060] The pressure-sensitive adhesive compositions obtained in Examples 1 to 7 had an excellent balance of tack (initial adhesive strength), adhesive strength, and holding strength.

[0061] Comparative Example 1 A pressure-sensitive adhesive composition was obtained in the same manner as in Example 1, except that an aliphatic petroleum resin (Quinton R100, manufactured by Zeon Corporation, softening point 98°C, Mn 1170, Mw 2290, bromine number 27) generally used in hot melt adhesive compositions was used instead of the cycloolefin copolymer. The evaluation results are shown in Table 2.

[0062] Comparative Example 2 A pressure-sensitive adhesive composition was prepared and evaluated in the same manner as in Example 1, except that cycloolefin copolymer D was used instead of cycloolefin copolymer A. The results are shown in Table 2.

[0063] Comparative Examples 3 to 4 Pressure-sensitive adhesive compositions were prepared and evaluated in the same manner as in Example 1, except that cycloolefin copolymer B was used in an amount shown in Table 2. The results are shown in Table 2. [Industrial Applicability]

[0064] According to the present invention, by blending a specific cycloolefin copolymer, it is possible to provide a pressure-sensitive adhesive composition having an excellent balance of good tack (initial adhesive strength), adhesive strength and holding power, and the industrial value of the composition is extremely high.

Claims

1. The pressure-sensitive adhesive composition contains 10 to 100 parts by mass of a process oil and 60 to 150 parts by mass of a cycloolefin copolymer relative to 100 parts by mass of a thermoplastic elastomer, wherein the cycloolefin copolymer has a softening point of 60 to 120°C, a bromine number of 10 to 60, and a number average molecular weight of 800 to 5,000.

2. 2. The pressure-sensitive adhesive composition according to claim 1, wherein the thermoplastic elastomer is a styrene-isoprene-styrene block copolymer.

Citation Information

Patent Citations

  • Method for testing colony

    JP1985083597A